Pengelolaan Zakat Melalui Program Bedah Rumah Oleh Pemkot Palembang dan Baznas - Ananda Tiara Puspita; Refi Prixline; Widya Marcelina; Febri Afrido; Maya Maya (CV. Publikasi Indonesia, 2023)
The purpose of this research is to examine and understand how zakat funds are managed for the people in Palembang City through a house renovation program implemented by the Palembang City Government and BAZNAS. This study uses qualitative data types, with secondary data sources taken from the official BPS (Central Statistics Agency) website documents such as data on population size, population density, poverty rate, and library research or literature that is relevant to the subject under study, such as books. libraries that are relevant to the problem under discussion. While the collection technique is observation, and some of the data is obtained from a number of articles and news. The results of this study indicate that the role of zakat management organizations such as BAZNAS and Palembang City Government in empowering communities in Palembang City is to prosper and make people become independent and creative through programs such as this house renovation.